Association of yield attributes among quantitative characters of cardamom (Elettaria cardamomum Maton) - Mohamed Sayed, V S Korikanthimath, D Prasath, A A (Journal of Spices and Aromatic Crops, 2000)
The correlation between quantitiative characters of cardamom (Elettaria cardamomum) on number of capsules per plant and fresh weight of capsules per plant was estimated. The number of capsules per plant had significant positive correlation with total number of tillers, bearing tillers and total panicles per plant, and fresh weight of capsules had significant positive correlation with number of tillers per plant and number of panicles per plant.